Technology Adoption and Peer Influence on Student AI Research Tools Purchase Intention - Ramadhan, Zidane; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Technological advancement has brought changes into how researchers conduct their research, Artificial Intelligence (AI) is one of the most impactful technologies that change the process. Through the lens of Technology Adoption Model (TAM) Framework, this research is aimed to uncover the relationship between technology adoption factors and peer influence in students’ intention toward buying AI research tools. Previous research is still limited toward explaining technology adoption toward students’ purchase intention and neglected social factors such as peer influence, therefore reinforcing the importance of the research. The study will be conducted on 100 State University of Jakarta students and Analysis of the data will use Partial Least Square (PLS) Structural Equation Model to explain the connection between variables.